Tango1 coordinates the formation of endoplasmic reticulum/Golgi docking sites to mediate secretory granule formation - Reynolds, Hayley M. (J Biol Chem, 2019)
Regulated secretion is a conserved process occurring across diverse cells and tissues. Current models suggest that the conserved cargo receptor Tango1 mediates the packaging of collagen into large coat protein complex II (COPII) vesicles that move from the endoplasmic reticulum (ER) to the Golgi apparatus. However, how Tango1 regulates the formation of COPII carriers and influences the secretion of other cargo remains unknown. Here, through high-resolution imaging of Tango1, COPII, Golgi, and secretory cargo (mucins) in Drosophila larval salivary glands, we found that Tango1 forms ring-like structures that mediate the formation of COPII rings rather than vesicles. These COPII rings act as docking sites for the cis-Golgi. Moreover, we observed nascent secretory mucins emerging from the Golgi side of these Tango1–COPII–Golgi complexes, suggesting that these structures represent functional docking sites/fusion points between the ER exit sites and the Golgi. Loss of Tango1 disrupted the formation of COPII rings, the association of COPII with the cis-Golgi, mucin O-glycosylation, and secretory granule biosynthesis. Additionally, we identified a Tango1 self-association domain that is essential for formation of this structure. Our results provide evidence that Tango1 organizes an interaction site where secretory cargo is efficiently transferred from the ER to Golgi and then to secretory vesicles. These findings may explain how the loss of Tango1 can influence Golgi/ER morphology and affect the secretion of diverse proteins across many tissues.